Behavioral and Social Factors Influencing Sweetened Condensed Milk Consumption in Toddlers in Semarang - Mardiana; Setyaningsih, Aryanti; Rokhmah, Farida Dwi (Journal of Health Education, 2025)
Background: Continuous consumption of sweetened condensed milk can inhibit the optimal growth and development of children aged 1-3 years. These consumption habits in toddlers impact their nutritional status, including the risk of being overweight, obese, and undernourished. This study aims to determine the determinants of sweetened condensed milk consumption in toddlers from a behavioral and social perspective in the Sekaran and Bandarharjo Health Center Area, Semarang City. Methods: This study employs quantitative research with observational and analytical methods, utilizing cross-sectional approaches. The respondents in this study were 100 toddlers residing in Sekaran and Bandarharjo Health Centers, Semarang City. The sampling technique employed was purposive sampling, and data analysis was conducted using univariate analysis with frequency distribution, bivariate analysis with the Pearson statistical test or Spearman Rank correlation (α = 5%), and multivariate analysis with logistic regression. Results: Approximately 35.8% of children had been provided with sweetened condensed milk for no less than twelve months, while 41.2% were reported to consume it three or more times within a single day. The elevated intake of sweetened condensed milk observed in this study demonstrated a statistically significant correlation with lower maternal educational attainment (p = 0.028). Notably, although 51.0% of surveyed mothers acknowledged that sweetened condensed milk is a sugar-laden beverage with added milk content, it is still administered to toddlers. Conclusions: In conclusion, despite over half of mothers recognizing sweetened condensed milk as a sugar-rich beverage with added milk, its frequent administration to toddlers—often three or more times daily and sustained for over a year—is significantly associated with lower maternal education levels, highlighting a critical gap in nutritional awareness and practice. The consumption of sweetened condensed milk among toddlers remains relatively high, and this elevated intake is influenced by maternal education